Washing obsessive-compulsive symptoms as adaptation—insights from a 3-year longitudinal cohort during the COVID-19 pandemic - Costa, Ana Daniela; Raposo-Lima, Catarina; Couto, Beatriz; Fernandes, Afonso; Machado-Sousa, Mafalda; Moreira, Pedro Silva; Ferreira, Sónia; Picó-Pérez, Maria; Morgado, Pedro (Frontiers in Psychology, 2025)
IntroductionStressful events are one cause for the emergence and/or worsening of obsessive-compulsive symptoms. The public health measures employed to prevent the contraction of the COVID-19 virus overlap with common behaviors adopted by people diagnosed with obsessive-compulsive disorder. Thus, we decided to study the longitudinal impact of the pandemic in the general Portuguese population assessed with the Obsessive-Compulsive Inventory (OCI-R), and the Depressive, Anxiety, and Stress Scale (DASS-21).MethodsOne hundred and eighty-nine participants reported their scores at three different time-points of the pandemic in Portugal: March of 2020, March of 2021, and March of 2022. Non-parametric repeated measures analyses were performed on the OCI-R and DASS-21 scores to analyze differences in the levels of symptomatology throughout time.ResultsWe found statistically significant differences with time in the OCI-R total and washing subscale scores, as well as in the anxiety subscale of DASS-21 score. For OCI-R total, we found significantly higher scores in 2020 compared to 2021 and 2022, and for the washing subscale we found statistically significant decreases with time. In terms of anxiety scores, we found significantly lower symptoms in 2021 compared to the others.ConclusionThe reliance on the washing-like behaviors to contain the pandemic spreading explains its augmented scores in the acute phases of the pandemic and thus the continuous decrease of symptomatology with time. For anxiety, both the beginning and the end of the pandemic seem to have posed a threat, leading to an increase in worry and hypervigilance. In general, our results demonstrate the adaptative nature of humans and the instrumental role of psychological distress to cope with the world around us.